PENGARUH LINGKUNGAN KERJA, BEBAN KERJA DAN STRES KERJA TERHADAP RETENSI KARYAWAN PADA PT. BERLIAN EKA SAKTI TANGGUH (PT. BEST) - Elyza Meynasari Purba; Yuli Arnida Pohan (Jurnal Widya, 2024)
This research aims to determine the influence of the work environment, workload and work stress on employee retention at PT. Tough Eka Sakti Diamond. The research uses a quantitative type of research. The data sources used in this research are secondary and primary data sources. The sample used in this research was 188 respondents whose type of sampling used a saturated sample. The testing techniques used in this research include research instrument tests, descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests. Based on the partial results obtained, it can be explained that the work environment variables, workload and work stress have an effect on employee retention at PT. Tough Eka Sakti Diamond. From the results of the simultaneous test it can be concluded that the work environment variables, workload and work stress together influence employee retention at PT. Tough Eka Sakti Diamond.